Green Marketing and Purchase Intention for Fore Coffee Products - Ismail, Taufiq; Aldiansyah, Mohammad Wildan (Universitas Muhammadiyah Yogyakarta, 2024)
Green marketing for coffee products is explored for its role on purchase intention. As concern on environmental matters is raising, green marketing becomes an important part to drive customers purchase intention, more over it is in the trending business in Indonesia like coffee product. This is an explanatory research with quantitative approach that used dichotomous data and logistic regression to measure and analyze Guttman’s scale. The data used in this study are primary data obtained through questionnaires distributed directly to coffee drink consumers in Malang Raya, involving 216 respondents. The results show that green marketing simultaneously affects the purchase intention of Fore coffee drinks by 24.5%. All three variables are significant in encouraging purchase intention including green product, green promotion, and green place. Yet, green price as assumed to be more expensive is required to remain affordable. The implications of these findings are expected to deliver theoretical contribution on green marketing as price remains sensitive for customers; in addition, it also provides practical contribution on how a green company should address this issue.